WATER BALANCE STUDY OF BHUBANESWAR-A DECADAL CHANGE - Paul, J.C.; Sahu, A.P.; Sharma, S.D. (Journal of Soil and Water Conservation, 2022)
Water balance is a very useful tool which allows for optimum utilisation Of water to take cam of the problem of decreasing per-capita availability of water. The parameters of water balance of 4 decades 1961-70, 1971-80, 1981- 90,1991-96 and for the normal year is found out using the climatic water balance method of Thornthwaite (1948). The average annual (1961-96) precipitation (P), potential evapotranspiration (PE), and actual evapotranspiration (AE) are 1479.5 nun, 1619 nun and 1195.5 nun, respectively. During November to May there is water deficit to the tune of 423.5 mm, August to October there is water surplus of 284 Min and June to July the soil is being recharged completely. An increase in PE and AE and decrease in water surplus from 1961-70 to 1991-96 is noticed. The precipitation remains almost same during the period.